Habitat preference of the dinosaurs from the Ibero-Armorican domain (Upper Cretaceous, south-western Europe) - Bernat Josep Vázquez López; Albert Sellés; Albert Prieto-Márquez; Bernat Vila (Swiss Journal of Palaeontology, 2025)
Abstract Paleoenvironmental preferences for Cretaceous dinosaurs at a regional scale have been mainly assessed in North America. In south-western Europe, the dinosaur-bearing formations ranging the late Campanian to the latest Maastrichtian encompass coastal and lowland environments that produced hundreds of fossil localities with evidence of titanosaurian sauropods, maniraptoran and abelisauroid theropods, and nodosaurid ankylosaurs, together with rhabdodontid and hadrosauroid ornithopods. In order to study environmental associations of dinosaur taxa, we have revised, updated, and expanded upon an existing database that compiles the occurrence and minimum number of individuals for the dinosaur-bearing formations spanning the upper Campanian to the uppermost Maastrichtian of South-Western Europe. Based on this database, the habitat preferences of dinosaur groups in the region were determined by means of statistical tests of independence. All chi-square tests showed positive, mostly moderate-to-strong, and statistically significant associations between the studied groups and the environment they inhabited. The analysis of the residuals indicated that most dinosaur groups preferred lowland environments (including, contrary to previous studies, nodosaurids). The only exception were abelisauroids, which showed no habitat preference. Our results concur with recent works indicating that titanosaur sauropods and hadrosauroids preferred inland environments but clearly disagree with others suggesting that the latter as well as nodosaurid ankylosaurs were positively associated with marine or coastal settings. Considering the changes in occurrence distribution throughout the Maastrichtian turnover in the region, both titanosaurians and nodosaurids probably stablished a feeding strategy-based niche partitioning with ornithopods, although additional data is required to confidently confirm this relationship.